Innovating Instrument Handover Techniques for Robotic Scrub Nurses - Scheppach Carl; Wagner Lars; Spinner Caroline; Jell Alissa; Wilhelm Dirk (Current Directions in Biomedical Engineering)
A proposed solution to address increasing scarcity of operating room (OR) nurses is the deployment of robotic scrub nurses (RSNs). One of the primary responsibilities of these robots is the handover of surgical instruments to the surgeon. Despite this tasks’ apparent simplicity, it requires great precision and timing, while seamless execution is essential for the surgical workflow. This paper outlines the unique challenges of the instrument handover process between a RSN and a surgeon taking place during laparoscopic surgery. After customizing existing solutions from different domains to meet the specific needs of laparoscopic surgery, we introduced these solutions to medical professionals in a simulated OR scenario, and performed a utility analysis to identify the most suitable solutions.